Management of Entrepreneurship Soft Skill Training for Santri Pondok Pesantren Fadhlul Fadhlan Mijen Semarang - Zakiyah, Amalia; Hakim, Lukmanul; Suryorini, Ariana (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
ABSTRACTThe current era of disruptive and Industrial Revolution has experienced an economic boom. But everyone is helping, rising poverty rates are caused by a lack of ability to change the times, especially in this fast-paced technological age. Therefore, the younger generation in the future must be able to manage themselves and have good abilities in terms of religion or the world as well as soft skills that are not less competitive so that they are not shaken by the onslaught of the times. So we need a generation of strong faith, and strong reason in critical thinking in solving any problem with creative and innovative abilities that should not be left behind. Islamic boarding schools are the right place for the Islamic generation, the cottage is the oldest place of education and can adapt to the times without changes like a hurricane. This research method uses descriptive qualitative research. Data collection techniques used in this study were observation, interviews, and documentation. Checking and checking the validity of the data is done through observation and triangulation of data. The data analysis technique was carried out in several stages starting from data reduction, data presentation, and conclusions. The results of this study are management training with elements of good training management and application of knowledge and the benefits of da'wah for students who are applied at the Fadhlul Fadhlan Mijen Islamic Boarding School Semarang. Keywords: Management, Entrepreneurship Soft Skills, Da'wah, Santri and Islamic Boarding Schools